Dufay - Fallows, David (London J. M. Dent & Sons LTD, 1982)
Dufay now stands unchallenged as the leading composer of the Middle Ages. Performances of his music are increasingly frequent, and most of it can be heard on commercial recordings, so it is time for a study of his life and work that attempts to show why he has found so much favour with performers and listeners today. Over the last 30 years and particularly over the last decade, an enormous burst of scholarly endeavour has added immeasurably to our knowledge of the subject. This book is primarily an attempt to assemble the most important of that information which was hitherto available only in the articles, dissertations and books produced in many parts of Europe and the United States. Includes 80 music examples, 12 pages of photographs, and three maps.